Preparation method of In2S3 (at) PDA / SA / PDMS / MS three-phase integral photocatalyst for producing H2O2

The gas-liquid-solid three-phase interface is constructed through In2S3@PDA/SA/PDMS/MS three-phase integrated photocatalyst, which solves the problem of insufficient accessibility of O2 in traditional photocatalytic systems, and achieves efficient H2O2 production and strong stability The photocatalytic effect provides a green and sustainable production method.

CN119237013AInactive Publication Date: 2025-01-03LIAONING UNIVERSITY

Patent Information

Application Number
CN202411338853.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When producing H2O2, the traditional biphase photocatalytic system has low photocatalytic efficiency due to insufficient accessibility of O2, and is difficult to recover and have limited light utilization, making it difficult to actually apply.

Method used

Three-dimensional flower-like In2S3@PDA/SA/PDMS/MS three-phase (gas-liquid-solid) integrated photocatalyst is synthesized by ion exchange method, and gas-liquid-solid three is constructed by hydrophobic treatment. Phase interface improves O2 accessibility and mass transfer efficiency.

Benefits of technology

It has achieved efficient H2O2 production, with a production capacity of 4.6mmol/g, with good stability and repeatability, solved the problems of O2 accessibility and recycling, and provided a green synthesis route and sustainable technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237013A_ABST
    Figure CN119237013A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of production of high value-added chemicals and catalysts, and particularly relates to a preparation method of an In2S3 (at) PDA / SA / PDMS / MS three-phase integral photocatalyst for producing H2O2. The preparation method comprises the following steps: preparing In-Co PBA nano-cubes through a precipitation reaction of InCl3 and K3 [Co (CN) 6], obtaining In2S3 through a one-step anion exchange reaction, loading polydopamine PDA on the surface of the In2S3 through an in-situ polymerization reaction to synthesize an In2S3 (at) PDA photocatalyst, mixing the In2S3 (at) PDA with sodium alginate SA hydrogel, and loading the mixture onto a PDMS modified melamine sponge MS to obtain the In2S3 (at) PDA / SA / PDMS three-phase (gas-liquid-solid) integral photocatalyst. Under the irradiation of visible light, the yield of H2O2 produced by the monolithic catalyst within 90 minutes reaches 4.6 mmol / g. The method has the characteristics of simplicity, convenience, high efficiency and low cost, and can be applied to photocatalytic production of H2O2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high value-added chemicals and catalyst production, and specifically relates to a method for preparing an In2S3@PDA / SA / PDMS / MS three-phase integral photocatalyst for producing H2O2. Background Art

[0002] As one of the 100 most important chemicals in the world, hydrogen peroxide (H2O2) has attracted more and more attention since it was first synthesized by Thenard in 1818. It is widely used in chemical, medical, energy, environmental and other fields. H2O2 is an efficient and green oxidant for environmental remediation due to its high active oxygen content and safe reactants (usually H2O and O2). In the bioremediation of contaminated aquifers, it is usually used as a supplement to the oxygen source and as an oxidant in advanced oxidation processes (AOPs) to produce ·OH through the Fenton reaction or ultraviolet radiation. H2O2 is also used for water disinfection and does not produce disinfection by-products, which is superior to traditional chemical disinfectants such as chlorine, ozone, chloramines, chlorine dioxide, etc., which produce disinfection by-products.

[0003] Solar-driven photocatalysis is a promising approach to produce H2O2 using light energy and photocatalysts, and has attracted widespread attention due to its sustainable characteristics. Conventional biphasic photocatalytic systems usually use suspended powder photocatalysts for photocatalytic production of H2O2. However, due to the limited solubility of O2 in solution, the accessibility of the photocatalyst to the O2 reactant is insufficient. In addition, conventional biphasic photocatalytic systems usually have other problems, such as difficult recycling, agglomeration, and limited light utilization. These problems restrict the efficiency of gas participation in photocatalytic reactions and are not conducive to practical applications.

[0004] Faced with these problems, many scholars have used different substrate materials and combined them with photocatalysts to derive supported photocatalytic reactors. Supported flat-plate reactors can avoid the sedimentation of photocatalysts and the complicated recovery process of powdered catalysts. However, the poor accessibility of O2 has not been solved. Therefore, in recent years, the construction of the gas-liquid-solid three-phase interface has attracted widespread attention and has been proven to be an effective strategy to promote the transfer of gaseous O2 to photocatalysts, thereby improving photocatalytic performance. Higher concentrations of oxygen can be in close contact with the electrons generated by the photocatalyst and the protons from the water at the three-phase interface, thereby enhancing the kinetics of the entire photocatalytic reaction. The photocatalytic system at the three-phase interface generally has the advantages of easy recovery, high stability, and strong repeatability, and will be a very effective strategy for producing H2O2. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing an In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst having high light response and capable of effectively separating photogenerated electrons and holes.

[0006] The second object of the present invention is to provide a method for preparing H2O2 using In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) integral photocatalyst.

[0007] The technical solution adopted by the present invention is:

[0008] A method for preparing an In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst comprises the following steps:

[0009] 1) InCl3 was dissolved in deionized water, and the mixture was stirred continuously until the solid completely disappeared. Then Na3C6H5O7·2H2O was added to form solution A. K3Co(CN)6 was dissolved in deionized water to form solution B. Then solution B was poured into solution A and stirred magnetically to make it completely mixed. The mixed solution was aged continuously at room temperature for 18 hours. The white precipitate was collected, centrifuged at 8000 rpm for 2 minutes, washed with ethanol and deionized water for 3 times, and dried at 60°C for 12 hours to obtain In-Co PBA nanocubes.

[0010] 2) dispersing the In-Co PBA nanocubes obtained in step 1) into anhydrous ethanol and stirring to form a uniform solution, adding thiourea and further stirring for 0.5 hours; transferring the obtained solution to a reactor for hydrothermal reaction, washing the yellow precipitate with deionized water and ethanol, and then vacuum drying at 60° C. to obtain In2S3 nanoflowers;

[0011] 3) dispersing the In2S3 nanoflowers obtained in step 2) in a Tris-HCl aqueous solution in which dopamine hydrochloride is dissolved; then, stirring the suspension at 25°C for 24 hours; centrifuging and washing with water and ethanol 4 times, and drying at 60°C for 12 hours to obtain an In2S3@PDA product;

[0012] 4) Ultrasonic dispersion of the In2S3@PDA obtained in step 3) in water for 5 min, then sodium alginate SA is added and further ultrasonicated to obtain a mixed hydrogel precursor In2S3@PDA and SA In2S3@PDA / SA; the cleaned MS is immersed in a n-hexane solution of PDMS, and the hydrophobically modified PDMS / MS is obtained after drying at room temperature; In2S3@PDA / SA is uniformly coated on the top layer of PDMS / MS, and immersed in a CaCl2 solution overnight to fully crosslink the hydrogel precursor, and the In2S3@PDA / SA / PDMS / MS three-phase integral photocatalyst is obtained after washing.

[0013] Furthermore, in the above-mentioned preparation method, in step 1), the mass ratio of InCl3:Na3C6H5O7·2H2O:K3Co(CN)6 is 177:220:133.

[0014] Furthermore, in the above preparation method, in step 2), the mass ratio of In-Co PBA to thiourea is 2:9.

[0015] Furthermore, in the above preparation method, in step 2), the hydrothermal reaction condition is 180° C. for 24 hours.

[0016] Furthermore, in the above-mentioned preparation method, in step 3), the mass ratio of In2S3 to dopamine hydrochloride is 20:3.

[0017] Furthermore, in the above-mentioned preparation method, in step 4), the mass ratio of In2S3@PDA:SA is 2:15.

[0018] Furthermore, in the above preparation method, in step 4), the concentration of the CaCl2 solution is 3wt%.

[0019] Application of the In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst prepared by any of the preparation methods described above in the photocatalytic preparation of H2O2.

[0020] Furthermore, the above-mentioned application method is as follows: the In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst is floated on a neutral aqueous solution without adding a sacrificial agent, one side coated with In2S3@PDA / SA is contacted with the aqueous phase, and the other side is exposed to O2, and the catalytic reaction is carried out under simulated sunlight at an ambient temperature of 25°C.

[0021] Furthermore, in the above application method, the simulated sunlight irradiation adopts a 300W xenon lamp as a light source, and the xenon lamp λ≥420nm.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention synthesizes a three-dimensional flower-shaped In2S3@PDA photocatalyst by an ion exchange method, further improving the light response, inhibiting the recombination of photogenerated electron-hole pairs, improving the utilization rate of electron holes, and improving the photocatalytic activity.

[0024] 2. The present invention uses In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst prepared by In2S3@PDA, constructs a gas-liquid-solid three-phase interface through hydrophobic treatment, solves the problems of poor oxygen solubility and high mass transfer resistance, is easy to recycle, has high stability and strong repeatability. Under visible light irradiation, the monolithic catalyst produces 4.6mmol / g of H2O2 within 90min, providing a green synthesis route and sustainable technology for the production of H2O2.

[0025] 3. The present invention is simple, efficient, low-cost and has high visible light absorption. The In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) integral photocatalyst has the characteristics of narrow band gap, large specific surface area, good conductivity, high catalytic activity, good visible light absorption performance and good stability, high separation efficiency of photogenerated electron-hole pairs, fast interfacial charge transfer efficiency, high photocatalytic preparation of H2O2 yield, and can be applied to the fields of photocatalytic preparation of hydrogen peroxide and degradation of organic matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are the SEM images (a) and TEM images (b) of the three-dimensional flower-like In2S3@PDA photocatalyst.

[0027] Figure 2 These are the XRD patterns of In2S3 and In2S3@PDA.

[0028] Figure 3 The transient photocurrent curve (a) and impedance curve (b) of In2S3@PDA and In2S3.

[0029] Figure 4 This is the SEM and corresponding hydrophobic angle diagram of the In2S3@PDA / SA / PDMS / MS three-phase integral photocatalyst, where (a) is the cross-section of the integral catalyst, (b) is the top of the integral catalyst, and (c) is the bottom of the integral catalyst.

[0030] Figure 5 It is the photocatalytic H2O2 production diagram of In2S3@PDA, In2S3@PDA / SA / MS, and In2S3@PDA / SA / PDMS / MS.

[0031] Figure 6 This is a diagram showing the effect of changing the O2 concentration in the liquid phase (a) / gas phase (b) on the production of H2O2 by In2S3@PDA / SA / PDMS / MS. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments.

[0033] Example 1 Preparation of In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst

[0034] 1) Dissolve 0.177g of InCl3 in 20mL of deionized water and continue stirring until the solid disappears completely; then add 0.220g of Na3C6H5O7·2H2O to form solution A. Dissolve 0.133g of K3Co(CN)6 in 30mL of deionized water to form solution B, then pour solution B into solution A and stir magnetically to mix them completely. The mixed solution is aged continuously at room temperature for 18 hours. Collect the white precipitate, centrifuge at 8000rpm for 2 minutes, wash 3 times with ethanol and deionized water, and dry at 60℃ for 12 hours to obtain In-Co PBA nanocubes.

[0035] 2) Dissolve 200 mg of In-Co PBA in 30 mL of anhydrous ethanol and stir to form a uniform solution, then add 900 mg of thiourea and stir for further 0.5 hours. Transfer the resulting solution to a reactor and react at 180 ° C for 24 hours. Wash the yellow precipitate In2S3 with deionized water and ethanol, and then vacuum dry at 60 ° C to obtain In2S3 nanoflowers.

[0036] 3) 200 mg of In2S3 was dispersed in 50 mL of Tris-HCl aqueous solution, in which 30 mg of dopamine hydrochloride was dissolved. Then, the suspension was stirred and reacted at 25°C for 24 hours. After centrifugation and washing with water and ethanol 4 times, it was dried at 60°C for 12 hours to obtain the In2S3@PDA product.

[0037] 4) Ultrasonic dispersion of 2 mg In2S3@PDA in 1.5 mL H2O for 5 min, then adding 15 mg SA, further ultrasonicated until uniform, to obtain a mixed hydrogel precursor In2S3@PDA and SA In2S3@PDA / SA. The cleaned MS was soaked in a 2.5 wt% PDMS n-hexane solution, and PDMS / MS was obtained after drying at room temperature. The hydrogel precursor liquid In2S3@PDA / SA was evenly coated on the top layer of PDMS / MS, and soaked in a 3 wt% CaCl2 solution overnight to fully crosslink the hydrogel precursor, and after washing, the In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) integral photocatalyst was obtained.

[0038] Figure 1 These are the SEM images (a) and TEM images (b) of the three-dimensional flower-like In2S3@PDA photocatalyst. It can be seen from the figures that the prepared In2S3@PDA has a three-dimensional flower-like structure and a rough surface.

[0039] Figure 2 It is the XRD diagram of In2S3 and In2S3@PDA. It can be seen that the obtained diffraction peak is consistent with the prepared cubic β-In2S3 (JCPDS: 32-0456) of In2S3, and due to the low content of PDA, the polymer presents an amorphous structure, and its XRD characteristic peak of In2S3@PDA has hardly changed.

[0040] Figure 3 Figure 1 is the transient photocurrent curve (a) and impedance curve (b) of In2S3@PDA and In2S3. From (a) the transient photocurrent curve, it can be seen that under illumination, the transient photocurrent increases rapidly. The transient photocurrent of In2S3@PDA is larger than that of In2S3, indicating that In2S3@PDA has a better photoelectric response. From (b) the impedance curve, it can be seen that the arc radius of In2S3@PDA is smaller than that of In2S3, indicating that the carriers are effectively transferred and separated.

[0041] Figure 4 This is the SEM and corresponding hydrophobic angle image of the In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst. From its cross-sectional image (a), it can be clearly seen that the top of the monolithic catalyst (b) is the hydrophobic side of the PDMS-modified MS, showing a large water contact angle (137.9°). The bottom of the monolithic catalyst (c) is the hydrophilic layer coated with the In2S3@PDA / SA photocatalyst. The In2S3@PDA / SA hydrogel is uniformly deposited on the MS skeleton, and the water contact angle is 17.3°.

[0042] Example 2 Application of In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst in photocatalytic preparation of H2O2

[0043] Here’s how:

[0044] The In2S3@PDA / SA / PDMS / MS three-phase (gas-liquid-solid) monolithic photocatalyst prepared in Example 1 was floated on a neutral aqueous solution without adding a sacrificial agent. One side of the coated In2S3@PDA / SA was exposed to the aqueous phase and the other side was exposed to O2. A 300W xenon lamp was used to simulate sunlight irradiation at an ambient temperature of 25°C. The xenon lamp λ≥420nm was used to perform a catalytic reaction under simulated sunlight irradiation. During the light-driven catalytic reaction, 0.5mL of the reaction solution was taken out every 30min, and the generated H2O2 was detected by spectroscopy.

[0045] (I) Effect of different catalyst materials on H2O2 generation

[0046] In2S3@PDA and In2S3@PDA / SA / MS were dispersed in neutral aqueous solution respectively without adding sacrificial agent. High-purity O2 was pumped into the solution to saturation under dark conditions. At an ambient temperature of 25°C, a 300W xenon lamp was used to simulate sunlight irradiation with a xenon lamp λ ≥ 420nm to carry out photocatalytic H2O2 production reaction.

[0047] The results are as follows Figure 5 As shown in Figure 2, compared with In2S3@PDA catalyst, the cumulative H2O2 production of In2S3@PDA / SA / MS can reach 1.75 mmol·g -1 , which is significantly better than In2S3@PDA (0.7mmol·g -1 , inactivated in 1 hour). This is due to the protectiveness of SA itself, which makes the In2S3@PDA / SA / MS composite hydrogel have high catalytic stability against the photocorrosion of In2S3@PDA itself, thereby maintaining the photocatalytic activity. After the introduction of the three-phase interface, the cumulative H2O2 concentration of In2S3@PDA / SA / PDMS / MS can reach up to 4.6mmol·g -1 , which is significantly better than In2S3@PDA / SA / MS. This increase is due to the introduction of the three-phase interface, which improves the O2 availability of In2S3@PDA / SA / PDMS / MS and synergizes with the protectiveness of SA to increase its H2O2 production efficiently and stably.

[0048] (II) Effects of different gas environments on H2O2 generation

[0049] N2, O2 and air were introduced into the reaction solution of the In2S3@PDA / SA / PDMS / MS three-phase photocatalytic system to change the O2 concentration in the liquid phase. In2S3@PDA / SA / PDMS / MS was used as a photocatalyst to catalyze the reaction for 1 hour to synthesize H2O2. The results are shown in Figure 6 (a) As shown. N2, O2 and air were introduced into the gas phase of the In2S3@PDA / SA / PDMS / MS three-phase photocatalytic system to change the O2 concentration in the gas phase. In2S3@PDA / SA / PDMS / MS was used as a photocatalyst to catalyze the reaction for 1 hour to synthesize H2O2. The results are shown in Figure 6 (b) as shown.

[0050] like Figure 6 As shown in (a), the change of O2 concentration in the reaction solution has almost no effect on the synthesis of H2O2, which shows that in the (gas-liquid-solid) three-phase system, the O2 concentration at the reaction interface does not depend on the O2 content in the solution. Figure 6As shown in (b), when the concentration of O2 in the gas phase increases, the rate of the catalytic reaction increases. When the concentration of O2 in the gas phase decreases, the rate of the catalytic reaction also decreases. This shows that the O2 of the In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst with gas-liquid-solid coexistence is directly and quickly transported from the gas phase to the reaction interface, which breaks the limitation of using the low solubility of O2 in the liquid phase and increases the concentration and accessibility of O2.

Claims

1. A method for preparing a three-phase monolithic photocatalyst In2S3@PDA / SA / PDMS / MS, characterized in that: The steps include: 1) Dissolve InCl3 in deionized water, continue stirring until the solid disappears completely, then add Na3C6H5O7·2H2O to form solution A; dissolve K3Co(CN)6 in deionized water to form solution B; then pour solution B into solution A and stir magnetically to mix them completely; the mixed solution is aged continuously at room temperature for 18 hours; The white precipitate was collected, centrifuged at 8000 rpm for 2 min, washed three times with ethanol and deionized water, and dried at 60 °C for 12 h to obtain In-Co PBA nanocubes; 2) dispersing the In-Co PBA nanocubes obtained in step 1) into anhydrous ethanol and stirring to form a uniform solution, adding thiourea and further stirring for 0.5 hours; transferring the obtained solution to a reactor for hydrothermal reaction, washing the yellow precipitate with deionized water and ethanol, and then vacuum drying at 60° C. to obtain In2S3 nanoflowers; 3) dispersing the In2S3 nanoflowers obtained in step 2) in a Tris-HCl aqueous solution in which dopamine hydrochloride is dissolved; then, stirring the suspension at 25°C for 24 hours; centrifuging and washing with water and ethanol 4 times, and drying at 60°C for 12 hours to obtain an In2S3@PDA product; 4) Ultrasonic dispersion of the In2S3@PDA obtained in step 3) in water for 5 min, then sodium alginate SA is added and further ultrasonicated to obtain a mixed hydrogel precursor In2S3@PDA and SA In2S3@PDA / SA; the cleaned MS is immersed in a n-hexane solution of PDMS, and the hydrophobically modified PDMS / MS is obtained after drying at room temperature; In2S3@PDA / SA is uniformly coated on the top layer of PDMS / MS, and immersed in a CaCl2 solution overnight to fully crosslink the hydrogel precursor, and the In2S3@PDA / SA / PDMS / MS three-phase integral photocatalyst is obtained after washing.

2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of InCl3:Na3C6H5O7·2H2O:K3Co(CN)6 is 177:220:

133.

3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of In-Co PBA to thiourea is 2:

9.

4. The preparation method according to claim 1, characterized in that: In step 2), the hydrothermal reaction condition is 180° C. for 24 hours.

5. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of In2S3 to dopamine hydrochloride is 20:

3.

6. The preparation method according to claim 1, characterized in that: In step 4), the mass ratio of In2S3@PDA:SA is 2:

15.

7. The preparation method according to claim 1, characterized in that: In step 4), the concentration of the CaCl2 solution is 3wt%.

8. Use of the In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst prepared by the preparation method described in any one of claims 1 to 7 in the photocatalytic preparation of H2O2.

9. The use according to claim 8, characterized in that: The method is as follows: the In2S3@PDA / SA / PDMS / MS three-phase monolithic photocatalyst is floated on a neutral aqueous solution without adding a sacrificial agent, one side coated with In2S3@PDA / SA is exposed to the aqueous phase, and the other side is exposed to O2, and the catalytic reaction is carried out under simulated sunlight at an ambient temperature of 25°C.

10. The use according to claim 9, characterized in that The simulated sunlight irradiation adopts a 300W xenon lamp as a light source, and the xenon lamp λ≥420nm.

Citation Information

Patent Citations

  • Co3S4 capable of serving as supercapacitor electrode material

    CN106629865A

  • Nickel-cobalt bimetallic sulfide based on PBA-etching-calcining vulcanization method and preparation method and application thereof

    CN116282236A

  • Hydrophobic NiS2 / In2S3 (at) PDMS photocatalyst for producing H2O2 and preparation method of hydrophobic NiS2 / In2S3 (at) PDMS photocatalyst

    CN117181305A

  • Composite catalyst for hydrogen production by photolysis of water as well as preparation method and application of composite catalyst

    CN117443412A

Cited By

  • Photothermal sponge based on hydrogel crosslinking fixed catalyst and preparation method and application thereof

    CN121085355A